Labeling dating abuse: Undetected abuse among Spanish adolescents and young adults - Luis Rodríguez-Franco (International Journal of Clinical and Health Psychology, 2012)
The Instituto de la Mujer in Spain highlights the existence of adult women being abused both with and without self-labeling as victims (situations of perceived abuse and technically abuse, respectively). The aims of this ex post facto study are assessing the existence of both types of abuse, and developing an alternative evaluation instrument for young couples, mixing behavioral items and a question on abuse perception (atomic and molecular evaluations). Using questions included in the Cuestionario de Violencia de Novios (CUVINO) we carried out two studies with different samples of adolescent and young women in school. The first one (N = 709; M = 18.5 years) replied the study conducted by the Instituto de la Mujer, finding 6.2% of women self-labeled as abused and 71% being technically abused. The second study (N = 1,327; M = 18.5) evaluated the relationship among different general perceptions (feeling abused, afraid and trapped in dating relationships), finding 5.8% of self-labeled abused women, 11.9% of afraid women, and 26.8% of women trapped in their relationships. Implications that these inconsistencies may have on prevention efforts are discussed.